2018
DOI: 10.1038/s41467-018-06804-y
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 receptor blockade blunts antigen-specific memory T cell responses and chronic inflammation in primates

Abstract: Targeting the expansion of pathogenic memory immune cells is a promising therapeutic strategy to prevent chronic autoimmune attacks. Here we investigate the therapeutic efficacy and mechanism of new anti-human IL-7Rα monoclonal antibodies (mAb) in non-human primates and show that, depending on the target epitope, a single injection of antagonistic anti-IL-7Rα mAbs induces a long-term control of skin inflammation despite repeated antigen challenges in presensitized monkeys. No modification in T cell numbers, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 69 publications
6
44
0
Order By: Relevance
“…Human infants with IL-7Rα mutations have severe T cell lymphopenia necessitating bone marrow transplantation (82). In contrast to most studies performed in rodent models where IL-7R blockade also induces broad lymphodepletion (21), administration of high doses of anti-IL-7Rα antagonistic mAb in baboons (83), cynomolgus monkey (84), or marmosets (85) did not induce lymphopenia or a significant decrease in peripheral T lymphocyte numbers. Similarly, early clinical results from phase I trials with 2 different antagonist anti-IL-7Rα mAbs, in healthy volunteers (GSK2618960; NCT02293161, ClinicalTrials.gov) or in type 1 diabetic adult patients (PF-06342674; NCT02038764), did not demonstrate induction of lymphopenia (86).…”
Section: Discussionmentioning
confidence: 98%
“…Human infants with IL-7Rα mutations have severe T cell lymphopenia necessitating bone marrow transplantation (82). In contrast to most studies performed in rodent models where IL-7R blockade also induces broad lymphodepletion (21), administration of high doses of anti-IL-7Rα antagonistic mAb in baboons (83), cynomolgus monkey (84), or marmosets (85) did not induce lymphopenia or a significant decrease in peripheral T lymphocyte numbers. Similarly, early clinical results from phase I trials with 2 different antagonist anti-IL-7Rα mAbs, in healthy volunteers (GSK2618960; NCT02293161, ClinicalTrials.gov) or in type 1 diabetic adult patients (PF-06342674; NCT02038764), did not demonstrate induction of lymphopenia (86).…”
Section: Discussionmentioning
confidence: 98%
“…In humans, mutations in the IL7Rα result in severe combined immunodeficiency (SCID) which is associated with the absence of T cells and normal numbers, nevertheless inactive, B cells 52 . Accordingly, targeting IL7Rα using specific antibodies may also affect T cells 53 and lead to immunodeficiency in patients. However, a recent study showed that treating healthy subjects with anti-human IL7R antibody was well tolerated and did not result in obvious alterations in immune cell populations and inflammatory cytokine profiles 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies (MAb) that antagonize the IL-7Rα (111) are in investigation for treatment of a range of autoimmune diseases and inflammatory conditions, including diabetes (112), multiple sclerosis, rheumatoid arthritis (113, 114), and inflammatory bowel disease (115). The aim of these approaches is to suppress aberrant memory CD4 + T cell responses (116).…”
Section: Therapeutic Implications Of Art-mediated Restoration Of Cd4+mentioning
confidence: 99%